2020
DOI: 10.1101/2020.01.24.917880
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Isolation and characterization of bovine herpes virus 5 (BHV5) from cattle in India

Abstract: 15Bovine herpesvirus 1 (BHV1) and 5 (BHV5) are genetically and antigenically related 16 alphaherpesviruses. Infection with one virus induces protective immunity against the other. 17However, disease associated with BHV1 and BHV5 varies significantly; whereas BHV1 18 infection is usually associated with rhinotracheitis and abortion, BHV5 causes encephalitis in 19 cattle. BHV5 outbreaks are sporadic and mainly restricted to the South American countries. 20 We report BHV5 infection for the first time fro… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Closely related alphaherpesvirus (BoHV-5) that was previously known as BoHV-1.3 is associated with encephalitis (Nandi et al, 2009). Antigenically and genetically, BoHV-1 and BoHV-5 are similar, it has been reported that BoHV-5 can be occasionally isolated from the respiratory tract because of its reactivation from latency in trigeminal ganglia and its secretion in nasal discharge (Marin et al, 2016;Kumar et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Closely related alphaherpesvirus (BoHV-5) that was previously known as BoHV-1.3 is associated with encephalitis (Nandi et al, 2009). Antigenically and genetically, BoHV-1 and BoHV-5 are similar, it has been reported that BoHV-5 can be occasionally isolated from the respiratory tract because of its reactivation from latency in trigeminal ganglia and its secretion in nasal discharge (Marin et al, 2016;Kumar et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The major envelope glycoproteins of BoHV-1 are gB, gC, gD (Niţă et al, 2010), glycoprotein B (gB) is a highly conserved gene and acts as a special target for BoHV-1 detection (Ros and Belák, 1999). Despite there were homology of gB genes among different strains of BoHV-1 (Whetstone et al, 1993), gB gene has enough diversity which allows the building of a phylogenetic tree that can be used to divide the virus into subtypes (Surendra, 2015;Kumar et al, 2020).…”
Section: Introductionmentioning
confidence: 99%